1-Ethyl-4-[1-(1-phenylethylidene)hydrazin-2-ylidene]-3,4-dihydro-1H-2λ(6),1-benzothiazine-2,2-dione - Shafiq, Muhammad (International Union of Crystallography, 2012)
In the title compound, C(18)H(19)N(3)O(2)S, the thiazine ring adopts an envelope conformation, with the S atom displaced by 0.732 (1) Å from the other atoms of the ring. The phenyl ring is oriented at a dihedral angle of 79.33 (7)° with respect to the fused benzene ring. The conformations about the two double bonds in the R (2)C=N—N=C(CH(3))Ar grouping are Z and E, respectively. In the crystal, inversion dimers linked by pairs of C—H⋯O interactions generate R (2) (2)(8) and R (2) (2)(12) loops, as parts of infinite chains along the a-axis direction.